A cross country perspective on Irish enterprise investment: Do fundamentals or constraints matter? - Eric Gargan; Eoin Kenny; Cynthia O'Regan; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2023)
Numerous research papers have used Irish-only data to test for the presence of an investment gap for small- and medium-sized enterprises (SMEs). In this paper, we use cross country firm-level survey data from the World Bank Enterprise Surveys to explore the investment patterns of Irish SMEs in a crosscountry context and test whether an investment gap is present when compared to other countries. We use an accelerator model of investment which links capital expenditure to firm output growth and test the sensitivity of investment to this key fundamental for Ireland and other countries. We then estimate whether Irish firms face an investment gap relative to their European peers. We test whether any differences in cross country patterns are driven by variation in financial factors (such as credit access or indebtedness) or firm quality (managerial experience, website usage, operating profitability). We find that Ireland's investment in fixed tangible assets is relatively well explained by these factors whereas a clear underinvestment in research and development expenditure emerges. Factors associated with investment in research and development include the degree of foreign technology usage, digitalisation and internationalisation.
Keywords: C1; C2; C3; C4; 330; SME Investment; accelerator model; access to credit; firm performance